RMB Internationalization and Currency Co-movement of Belt and Road Initiative Countries: Evolution and Impact Analysis - Cai, Jieting (Journal of Global Economy, Business and Finance, 2025)
Since the launch of the pilot program for RMB settlement in cross-border trade in 2009, the process of RMB internationalization has advanced steadily, achieving significant milestones in cross-border trade and investment settlement, the development of offshore RMB markets, and currency swap agreements. Between 2013 and 2023, the exchange rate co-movement between the RMB and the currencies of Belt and Road Initiative (BRI) countries gradually increased, and the RMB’s position in the global currency market has continued to rise. To examine the degree of linkage between the RMB and the currencies of BRI countries, as well as the evolution of its monetary influence, this paper first selected 91 representative currencies from BRI countries, estimates the exchange rate linkage between the RMB and other currencies, and applies the PMFG algorithm to construct an exchange rate co-movement network for analysis. Furthermore, the paper explores changes in the RMB’s influence during the progression of the BRI and compares its influence with that of the U.S. dollar and the euro in the region.